Atividade microbiana em função da salinidade do solo - Freitas, Fernanda Cristina de Morais (2016)
Salinity is a factor of great concern on soil degradation and is a threat to the microbial communities, and it prevents the release of soluble compounds in water and restricts the metabolic capacity of microorganisms to biodegrade. It increases the respiratory rate of the microbiota, which indicates high microbial activity, however, due to the negative effects of salinity, microbial activity tends to decrease. The present study aimed to evaluate the microbial activity of two different types of soils, Oxisols and Inceptisols, from agricultural areas located in the state of Rio Grande do Norte. The soils were distributed in sealed bottles, arranged in a randomized block design (RBD) and arranged in a saturated paste extract factorial of scheme 2 x 5 x 2, referring to the two soils, the five ECe (electrical conductivity in the saturated paste extractand two doses of organic material (presence or absence) and, tested in triplicate. The indirect measurement of microbial activity was determined according to the Standard Specifications of the Bartha Respirometric Method, adapted. Then, the regression of CO2 was taken against time for all treatment and for the evaluation of the final CO2 production, the surface response model was used. The experiment, conducted by 133 days of incubation, found a production of CO2 always higher in treatments with the addition of organic matter than in its absence, considering the same ECe. The CO2 production was obtained by the Oxisols, the treatments with and without organic matter, was in T40 and T41, referring to treatments with the highest ECe in the absence and presence of organic matter, respectively; on the CO2 production rate, salinity not affected and, in the presence of organic material, the treatments showed higher values than the control. In Inceptisols, CO2 production increases in the presence of organic matter, but decreases with increasing salinity, whose effect was also observed for the CO2 production rate. So, there was a difference in salt tolerance between soils, although the addition of organic matter has improved microbial activity in different salinities